Tokenism and job satisfaction for policewomen - Krimmel, John T. (American journal of criminal justice, 2003)
Women law enforcement officers from New Jersey and Pennsylvania participated in a self-administered anonymous survey. The objective of this study was to capture the respondent’s attitudes toward work and ascertain their levels of job satisfaction using Wharton and Barton’s (1991) job satisfaction scales. Their levels of job satisfaction were correlated with the proportion of women in their respective departments. Using Kanter’s (1977) concept of tokenism, it was found that those women who made up less than 15% of their department experienced less job satisfaction, greater levels of job-related depression, and lower self-esteem than those women working in departments where their numbers comprised greater than 15% of their departmental sworn personnel.